1978
DOI: 10.1104/pp.61.4.675
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Induced Wound Ethylene from Excised Segments of Etiolated Pisum sativum L., cv. Alaska

Abstract: Wound-induced ethylene synthesis by subapical stem sections of etiolated Pisum saivum L., cv. Alaska seedlngs, as described by Saltveit and Dilley (Plant Physiol 1978 61: 447450), was half-saturated at 3.6% (v/v) 02 and saturated at about 10% 02. Corresponding values for CO2 production during the same period were 1.1% and 10% 02, respectively. Anaerobiosis stopped all ethylene evolution and delayed the characteristic pattern of wound ethylene synthesis. Exposing tissue to 3.5% CO2 in air in a flowthrough s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…Autoinhibition of ethylene production has been described in various plant tissues (12,14,15,20,21). The present study shows that it also occurs in peel tissues of citrus fruit.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Autoinhibition of ethylene production has been described in various plant tissues (12,14,15,20,21). The present study shows that it also occurs in peel tissues of citrus fruit.…”
Section: Discussionmentioning
confidence: 57%
“…Autoinhibition of ethylene production in grapefruit flavedo discs occurs at about the same concentration range (Fig. 4) reported for other tissues (14,15,20,21).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Kawase (7) also reported a stimulation of ethylene production by anaerobic stress in sunflower stems. Saltveit and Dilley (9) showed that an anaerobic stress would induce 1.16* * Difference from control significant at P < 0.05; *** difference from control significant at P < 0.001. a rise in ethylene production similar to that which followed physical wounding of pea epicotyls. Both wounding and anaerobiosis increase ethylene synthesis in excised tomato roots (6).…”
Section: Resultsmentioning
confidence: 96%
“…In this way a higher ACC level may partly relieve the reduction of the specific activity of ACC oxidase brought about by oxygen shortage. As a result of the opposing effects of submergence on ACC synthase and ACC oxidase, hypoxia leads to a net inhibition of ethylene production in most plant species that have been studied (Saltveit and Dilley, 1978;Konze et al, 1980;Raskin and Kende, 1983;Pearce et al, 1992) and a net stimulation of ethylene production in maize roots (Jackson et al, 1985;Atwell et al, 1988;Brailsford et al, 1993) and rice internodes (Raskin and Kende, 1984). In both Rumex species, the balance between an increased availability of ACC synthase and a reduction of the specific activity of ACC oxidase may determine the net negative effect of submergence on the ethylene production rate.…”
Section: Balance Sheets For Ethylene Biosynthesismentioning
confidence: 99%